Comparison Study of Red Blood Cells and their Characteristics in Female Camels and their Male Calves in Libya - Altief, Tarek A.S.; Amir, Moneam A.; Sabir, Salem A.; Amaizik, Salem A. (Al-Mukhtar Journal of Sciences, 2022)
The study was conducted to comparison study of red blood cells and their characteristics in female camels and their male calves in Libya in the central region of Libya for a period of one year on three camels, male calves were selected according to birth. (MCH) and (MCHC) were evaluated in the blood of the mothers, and they were found to be significantly higher (P<0.05) than in the mothers. (Hb) and (MCH) for both mothers and calves increased significantly (P<0.05) at birth during the seasons. Whereas, the spring and summer seasons (MCH) in calves were significantly higher (P<0.05) than the mothers. The summer RBCs were significantly (P<0.05) higher for mothers than for calves. (Hb) and (MCV) for both were significantly higher in autumn (P<0.05) compared to other seasons. During the spring and summer seasons, the MCHC in the mothers was significantly (P<0.05) higher than in the calves. (PCV), (MCV), (MCH), and (MCHC) of mothers at birth were significantly (P<0.05) higher than calves, and higher for both during different months. The highest value of (MCV) for the two animals during the eighth month was significantly higher (P<0.05) than the values of the months excluding delivery. Also, the (MCH) of the calves was significantly higher (P<0.05) during the fifth month than that of the mothers. The value of (MCHC) increased in calves than mothers from the fifth month until the end of the study. We conclude from the foregoing that the calves adapt to the environment and keep pace with the adult animals after their fifth month.